Analysis of Depreciation Policy Based on Effective Tax Rate - Shah, Krishna Kumar (Academic Voices: A Multidisciplinary Journal, 2015)
Depreciation is an income tax deduction that allows a tax payer to recover the cost. It is an annually allowance for the wear and tear, deterioration or obsolesce of property .With the introduction of income tax Act 2002 the government claimed that the depreciation rule under the new law is more generous than the depreciation rule in 1992 in case of all the assets including machinery and building. This article compares Effective Tax Rate (ETR) which shows no decrease in 2002 in compassion to 1992 in ETR. It means the depreciation rule of 2002 in case of building and machinery is not generous as claimed by the tax policy maker. In contrary to this, the analysis shows that the depreciation provision of 1992 and 2002 are more liberal than the depreciation provision of 1982. DOI: http://dx.doi.org/10.3126/av.v4i0.12352 Academic Voices Vol.4 2015: 21-23